Ultrastructural features of the fat body and oenocytes of Rhinocricus padbergi Verhoeff (Diplopoda, Spirobolida) - Mathias, Maria Izabel Camargo [UNESP]; Fontanetti, Carmem Silvia [UNESP] (My University, 2000)
The fat body of the diplopod Rhinocricus padbergi is located in two preferential areas of its body: a) immediately below the tegument, denominated parietal, and b) filling the body cavity, close to the viscera, mainly the ovaries and alimentary canal, denominated perivisceral. Ultrastructurally, its cells, the adipocytes, presented varied morphology and contained organelles indicating that they are cells that mainly produce and store lipids and proteins. The presence of cells similar to the oenocytes found in insects was observed for the first time in diplopods, associated to the fat body of R. padbergi. Our observations suggest that this tissue probably maintains activity cycles, since the presence of cells undergoing apoptosis was detected.
Keywords: Apoptosis; Diplopoda; Fat body; Oenocytes; Rhinocricus padbergi; Ultrastructure